The correlation between nurses’ self-esteem and job satisfaction in Educational hospitals of Khorramabad in 2014 - Dabirian, azam; Malekipour, siran; Darvishpoor Kakhki, ali; Mehrabi, yadolah (Advances in Nursing & Midwifery, 2015)
Abstract Backgroun and aim: Self-esteem is the basic structure and essence of self-assessment and positive selfperception as one of the potential variables of job satisfaction. Employees’ job satisfaction is a career attitude, is an important variable for providing better services. The aim of this study is the determination the correlation between nurses’ self-esteem and job satisfaction in teaching Khorramabad , Iran in 2014. Method and Materials: This descriptive study was carried out in Khorramabad, Iranr in 2014. A convenient sample of 170 nurses participated in the study . Data were collected by 3 questionnaires : demographic characteristics of participants, Cooper-Smith Self-Esteem Inventory, and Wysocki & Chrome Job Satisfaction Scheme. ،The validity of questionnaires was assured by content validity method. The reliability of the instruments was determined by computing Chronbach’s Alpha . The questionnaires were distributed to nurses working in different shift works, which were completed and returned . Data were analyzed using SPSS 18 software. Results: Considering the self s steem scores of nurses , 25.9% were classified , as being at low self esteem level, 55. 9% at the average level and 18. 2% at the high self esteem level, while 23. 5% were at the low job satisfaction level, 64. 7% were at the average job satisfaction level and 11. 8% in were at the high job satisfaction level. Spearman correlation coefficients for correlation between self-esteem and job satisfaction was(r = 0. 381) (p = 0. 001) ,which shows a significant correlation between self-esteem and job satisfaction. The spearman correlation coefficients for age/work experience and self-esteem were (r = 0. 132) and (r = 0. 154), respectively, (p = 0. 086) and (p = 0. 045), respectively. There is a significant correlation between self-esteem and work experience, yet there is no significant correlation between self-esteem and age. The spearman correlation coefficients between ,work experience and job satisfaction were (r = 0. 278) and (r = 0. 274), respectively, (p = 0. 001). The correlation between age and job satisfaction is significant. Conclusion: According to the research results, it could be mentioned that there is a relationship between both variables of self-esteem and job satisfaction among the nurses. It is recommended to consider self-esteem and its promotion methods as a strategy to increase nurses’ job satisfaction. Keywords: self Esteem, job satisfaction, nurses.